HIV Serodisclosure and Sexual Behavior During International Travel. Issue 7 (July 2016) - Truong, Hong-Ha M.; Chen, Yea-Hung; Grasso, Michael; Robertson, Tyler; Tao, Luke; Fatch, Robin; Curotto, Alberto; McFarland, Willi; Grant, Robert M.; Reznick, Olga; Raymond, H. Fisher; Steward, Wayne T.
Abstract : Abstract: When traveling internationally, HIV serodisclosure and knowledge of partners' serostatus were hampered by the lack of a common language. Condomless anal intercourse was less likely to occur in partnerships where HIV serostatus was not disclosed or known. Taken together, these observations suggest that language barriers may affect sexual decision making. Abstract : A probability-based sample of gay and bisexual men from the San Francisco Bay Area found that language barriers can complicate human immunodeficiency virus prevention communication and behaviors during international travel.